Teaching Materials Analysis: The Place of Culture in English Teaching Materials Used in an International School in Budapest - Dogan Ger, Songul (Working Papers in Language Pedagogy, 2021)
With the increased mobility that has given rise to globalization, intercultural competence has become a necessity. Throughout the world, international schools in which English is used as the language of instruction aim to develop their students’ language skills and intercultural competence. To achieve this, teachers in these schools follow curricula and use teaching materials that enable the teaching of culture. The analysis of teaching materials to determine what kind of culture is being presented, and whether it is being taught critically and deeply, is therefore essential. In the present study, a research instrument was piloted that was designed for subsequent use in larger-scale research by the author on the development of cultural diversity awareness (CDA) and intercultural communicative competence (ICC). The present pilot study is based on the thematic content analysis of teaching materials used in the upper primary classes of an international school in Budapest. The findings revealed that the materials include a variety of culture-related activities with elements of big C, little c, and deep culture. Cultural activities, and the respective guidance for teachers included in the analyzed teaching materials, are transferrable to the contexts of English as a second language (ESL) and English as a foreign language (EFL).